THE EFFECT OF PERCEPTIONS OF TAXPAYER PERSONNEL OF FREE EMPLOYMENT ON TAX RATE AND PENALTY RATE ON TAX EVASION (Empirical Study: KPP MULYOREJO) - Mujahid Ma’ruf; Elia Mustikasari (Universitas Airlangga, 2018)
The aim of this research is to test about taxpayer’s perception of freelance of tax rate and penalty rate toward tax evasion.The dependent variable in the study was perception of tax evasion. The independent variable research were perception of tax rate and penalty rate. Population in this research is freelance taxpayers who have taxpayment card. The amount of sample used is 100 respondens collected with accidental sampling. Data program using SPSS (Statistical Product and Service Solution) version 18. Analysis method used in this research is multiple linear regression, determination coefficients (R2), and differential test of t-test.The research results showing that tax rate variable has the positive significant influence to tax evasion. Penalty rate has the negative significant influence to tax evasion.